Effects of 8 Weeks Feeding Diet with Low and High Isoflavones Soy Protein Concentrate on Serum Isoflavones in Non-alcoholic Fatty Liver Disease (NAFLD) Rat Model. (14th June 2022) - Hakkak, Reza; Twaddle, Nathan; Spray, Beverly; Irby, David; Korourian, Soheila
Abstract: Objectives: To examine the effects of 8 weeks feeding of low and high isoflavones levels in soy protein concentrate on the total serum isoflavones in a NAFLD obese rat model. Methods: 42 six-week old lean (L, n = 21) and obese (O, n = 21) Zucker rats were randomly assigned to 1 of 3 dietary groups: casein diet (C = control), soy protein with low isoflavones (LIF), or soy protein with high isoflavones (HIF) for 8 weeks (n = 7 rats/group). Rats were weighed twice weekly. After 8 weeks, all rats were sacrificed and serum for total isoflavones (genistein, daidzein and equol) were measured using a validated UPLC-MS/MS method and quantified utilizing stable-labeled internal standards. Results: Obese rats gained significantly more weight (P < 0.0001) than lean rats for all three diet groups. There was no detectable serum IF for both LC and OB groups. The mean ± SD for LIF vs HIF serum total IF (uM) for genistein were; (0.11 + 0.04 vs 2.55 + 1.04; p < 0.001), daidzein (0.07 + 0.02 vs 1.14 + 0.45; p < 001) and equol (0.07 + 0.03 vs 1.84 + 0.8; p < 0.001). For OLIF vs OHIF serum genistein were; (0.22 + 0.08 vs 3.69 + 1.52; p < 0.001), daidzein (0.12 + 0.04 vs 1.58 + 0.70; p < 001) and equol (0.06 + 0.03 vs 2.40 + 0.7; p < 0.001). Comparing serum genistein LLIF vs OLIF; p < 0.05 for Daidzein p < 0.05 and equol p = 0.86. Conclusions: High isoflavones soy protein concentrate compared to low isoflavones increased serum genistein and daidzein but had no effects on serum equol in a NAFLD rat model. Funding Sources: This project is support USDA #12889791 to RH.